Assessing Academic Workload in Computing Engineering Programs: A Preliminary Study - Joglar-Campos, C; Villalobos-Cid, M; Chourio-Acevedo, L (ASOC COLOMBIANA, FAC INGENIERIAS, 2025)
Assessing academic workload is a critical component of the educational process, given its importance in the health and performance of students. Several universities worldwide have evaluated their programs using academic credit systems as a reference by contrasting the expected and real academic workload through strategies based on surveys, focus groups, questionnaires, and logbooks. In this work, we perform a preliminary study by extracting information for curricular updating of our computing engineering programs based on academic workload. The related method is divided into four stages: (1) the designing of an informatic tool to manage the class-to-class activities; (2) the recording of the academic workload expected by academics; (3) the application of surveys to record the workload declared by students; (4) and the formulation of recommendations based on a mixed analysis that combines qualitative and quantitative elements. This preliminary study can be extended by analysing other educational contexts.